Isoquercitrin Ameliorates Cisplatin-Induced Nephrotoxicity Via the Inhibition of Apoptosis, Inﬂammation, and Oxidative Stress - Wang, Hao; Xia, Weiwei; Long, Guangfeng; Pei, Zhiyin; Li, Yuanyuan; Wu, Mengying; Wang, Qian; Zhang, Yue; Jia, Zhanjun; Chen, Hongbing (Frontiers in Pharmacology, 2020)
Cisplatin is extensively used and is highly effective in clinical oncology; nevertheless, nephrotoxicity has severely limited its widespread utility. Isoquercitrin (IQC), a natural flavonoid widely found in herbage, is well known and recognized for its antioxidant, anti-inflammatory, and anti-apoptotic properties. However, the potential effects and mechanism of IQC in cisplatin-induced acute kidney diseases remain unknown. In this study, we postulate the potential effects and mechanism of IQC upon cisplatin exposure in vivo and in vitro. For the in vivo study, C57BL/6J mice were pretreated with IQC or saline (50 mg/kg) by gavage for 3 days before cisplatin single injection (25 mg/kg). Renal function, apoptosis, inflammation, oxidative stress and p-ERK were measured to evaluate kidney injury. In vitro, mouse proximal tubular cells (mPTCs) and human proximal tubule epithelial cell line (HK2) were pretreated with or without IQC (80 μM for mPTCs and 120 μM for HK2) for 2 h and then co-administrated with cisplatin for another 24 h. Apoptosis, inflammation, ROS and p-ERK of cells were also measured. In vivo, IQC administration strikingly reduced cisplatin-induced nephrotoxicity as evidenced by the improvement in renal function (serum creatinine and blood urea nitrogen), kidney histology (PAS staining), apoptotic molecules (cleaved caspase-3, caspase-8, and Bcl-2), inﬂammatory cytokines (IL-1IL-6, TNF- and COX-2), oxidative stress (MDA and total glutathione) and p-ERK. In line with in vivo ﬁndings, IQC markedly protected against cisplatin-induced cell injury in mPTCs and HK2 cells. Collectively, these ﬁndings demonstrated that IQC administration could significantly protect against cisplatin nephrotoxicity possibly through ameliorating apoptosis, inflammation and oxidative stress accompanied by cross talk with p-ERK. Furthermore, IQC may have potential therapeutic uses in the treatment of cisplatin-induced acute kidney injury.